Management of slum settlements in urban areas is related to the principle of sustainable development goals in Indonesia - Endah, Kiki; Rusli, Budiman; Kartini, Dede Sri; Utami, Sawitri Budi (CENTRAL ASIA AND THE CAUCASUS, 2024)
Indonesia has a very high population density. This causes all kinds of problems. One of the most prominent problems is the problem of slum settlements. Slum settlements are also one of the daiturs in the sustainable development goals ratified by Indonesia as a program to improve Indonesia's welfare. The Indonesian government in this case has made many efforts to reduce the level of slum settlements in urban areas, one of which is by issuing various regulations to reduce the level of slum settlements.